Penentuan Rute Pendistribusian Gas LPG Dengan Metode Algoritma Nearest Neighbour (Studi Kasus Pada PT. Graha Gas Niaga Klaten) - Kurniawati, Dian; , Nurul Hidayati, PhD; , Ir. Agus Riyanto, MT (2015)
This research is focused on the comparison of the characteristics of route service between the existing conditions and the results of the Nearest Neighbor (NN) Method. The parameters used to compare consist of total distance and total travel time that is used in the distribution of the LPG gas cylinders. To answer the problems associated with the NN Method, the initial data should be prepared are distance matri x and savings matrix. The result were obtained: total distance distribution of existing condition is 2.071,2 km with a total travel time of 66 hours 6 minutes. The values are different from the NN Method calculation, in which a total distance of 1.483,6 km of distribution obtained with a total travel time of 59 hours 49 minutes. Based on these results, it can be said that the NN Method produces a better route characteristic.